Option pricing under stochastic environment of volatility and market price of risk - Phewchean, N; Wu, Yong Hong; Lenbury, Y (North Atlantic University Union (N A U N), 2013)
Since Black-Scholes model was proposed in 1973, it has been applied widely for option pricing. The aim of this paper is to develop European option pricing model taking into account stochastic volatility and stochastic market price of risk (MPR) under the framework of Black-Scholes. Both volatility and market price of risk are assumed to be stochastic and assumed to follow Ornstein-Uhlenbeck process. By using an analytical approach of Abraham Loui, explicit formulas are derived for European call and put option prices. Sensitivity of option price to model parameters are tested and the simulation results show the strong characteristic of stochastic model.